The potential of bottom ash as fine aggregate replacement in concrete - Mohd Azim, Muhammad (2010)
Bottom ash is one type of the solid residues by products produced from coal power generating plants. The purpose of this study was to enable the practical use of this material as an alternative to the existing building material. Direct use of this material with a large quantity, will provide a solution to dispose of this material, and the possibility as alternative materials in construction. The study was conducted to investigate the effect of replacing the bottom ash as fine aggregate (sand) in concrete on compressive strength and total porosity. Study was carried out by the sand replacement ratio of 25%, 50% and 100%. The control parameter is water-cement ratio at 0.46 and workability on 30-60 mm. Slump test have been conducted on wet concrete to evaluate the workability of concrete and the compressive strength is determined at the age of seven, 14 and 28 days of hardened concrete cube sample size of 150 mm. Meanwhile, for total porosity was measured with hardened concrete cube of 70 nun at 60 days age. The replacement of bottom ash on the sand in the concrete resulted in a decrease of slump test and compression test. The test results also showed porosity of concrete with bottom ash is higher than the control concrete. The analysis also showed that the compressive strength is inversely proportional to the porosity, which is the increment of porosity; it will reduce the compressive strength of concrete.